Banks’ Motivations for Designating Securities as Held to Maturity - Kim, Sehwa; Kim, Seil; Ryan, Stephen G. (The Accounting Review, 2025)
ABSTRACT We provide evidence that banks classify fixed-rate debt investment securities as held to maturity (HTM) rather than as available for sale (AFS) when HTM classification provides preferred financial accounting and regulatory capital treatments, not because they have a distinct economically motivated intent and ability to hold the securities to maturity. Specifically, we document predictably divergent security classifications by three categories of banks that differ in whether the regulatory accumulated other comprehensive income (AOCI) filter, which removes AOCI from Tier 1 capital, applies in four subperiods of our 2012–2022 sample period. The boundaries of the subperiods reflect changes in the AOCI filter’s applicability in 2014 and 2019 and the sharp rise in interest rates beginning in late 2021. We further find that the bank categories differ in the interest rate risk of their AFS securities and the extents to which they economically hedge that risk using derivatives and uninsured deposits. JEL Classifications: G21; G28; M41; M48.